2019
DOI: 10.5194/esd-10-121-2019
|View full text |Cite
|
Sign up to set email alerts
|

The role of moisture transport for precipitation in the inter-annual and inter-daily fluctuations of the Arctic sea ice extension

Abstract: Abstract. By considering the moisture transport for precipitation (MTP) for a target region to be the moisture that arrives in this region from its major moisture sources and which then results in precipitation in that region, we explore (i) whether the MTP from the main moisture sources for the Arctic region is linked with inter-annual fluctuations in the extent of Arctic sea ice superimposed on its decline and (ii) the role of extreme MTP events in the inter-daily change in the Arctic sea ice extent (SIE) wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Together with horizontal moisture convergence, anomalous intrusions of moisture may lead to anomalous precipitation, especially if forcing conditions favor enhanced condensation. Likewise the greenhouse effect or even cloud formation, the relationship between precipitation and ice melting is still unclear, and the effects of Arctic precipitation depend on the type of the precipitation and the season (e.g., Gimeno‐Sotelo et al, , ; Vihma et al, and references therein). In general terms, major flooding will favor the formation of superimposed ice, which will result in a increased ice thickness over the sea.…”
Section: Effects Of Moisture Gain On the Arctic Ice Floementioning
confidence: 99%
See 1 more Smart Citation
“…Together with horizontal moisture convergence, anomalous intrusions of moisture may lead to anomalous precipitation, especially if forcing conditions favor enhanced condensation. Likewise the greenhouse effect or even cloud formation, the relationship between precipitation and ice melting is still unclear, and the effects of Arctic precipitation depend on the type of the precipitation and the season (e.g., Gimeno‐Sotelo et al, , ; Vihma et al, and references therein). In general terms, major flooding will favor the formation of superimposed ice, which will result in a increased ice thickness over the sea.…”
Section: Effects Of Moisture Gain On the Arctic Ice Floementioning
confidence: 99%
“…Firstly, for example, some evidence is apparent of an increase in moisture transported from the extratropics to polar regions during the spring, with a consequent increase in the radiative forcing of water vapor contributing to melting (Kapsch, Graversen, & Tjernström, ); secondly, there has been an apparent increase in moisture transport in winter, related to an increase in precipitation in catchments that drain into the Arctic, which subsequently produces an increase in summer discharge and contributes to Arctic Ice Melting (Zhang et al, ). The implications of moisture transport for precipitation on the Arctic SIE are diverse and difficult to quantify, because the changes in precipitation are associated with opposing mechanisms, depending on the form of precipitation (rain or snow), as well as its intensity and seasonality (Gimeno‐Sotelo, Nieto, Vázquez, & Gimeno, , ; Vihma et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…By separating the planetary and synoptic-scale waves, Graversen and Burtu (2016) showed that latent heat transport, as a component of AMET, influences the Arctic warming with reanalysis data. Gimeno-Sotelo et al (2019) studied moisture transport with reanalysis data and observations, and showed that the moisture sources in the Arctic region are linked with interannual fluctuations of Arctic sea ice. Nummelin et al (2017) analyzed the linkages between OMET, ocean heat content (OHC) and AA through climate model simulations within the Coupled Model Intercomparison Project phase 5 (CMIP5).…”
Section: Introductionmentioning
confidence: 99%
“…In the Arctic, precipitation is expected to increase by 50% by 2100, and most of the precipitation will then be in the form of rain (Kattsov et al, 2007;Perovich et al, 2009;Screen and Simmonds, 2012;Bintanja and Selten, 2014). The influence of moisture transport in the Arctic is variable because changes in precipitation are related to patterns in atmospheric circulation and depend on the moisture (Gimeno-Sotelo et al, 2018;Gimeno-Sotelo et al, 2019). The transfer of moisture from the temperate zone to the polar regions in spring is increasing, and the increase in radiation emitted by moisture contributes to the melting of the sea ice (Kapsch et al, 2013) Arctic precipitation has a significant effect on navigation monitoring, sea ice, and climate cycles, and can be used to analyze and forecast the environmental status of the Arctic (Francis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%